Innovative Approaches for Tourism's Energy Challenge - Fernandez, Eneida; Romo, Zayra (World Bank, Washington, DC, 2012)
According on climate change and tourism the industry 'must rapidly respond to climate change, within the evolving United Nation (UN) framework and progressively reduce its Greenhouse Gas (GHG) contribution if it is to grow in a sustainable manner.' In Latin America and the Caribbean (LAC), fossil fuel accounts for about 75 percent of energy needs, creating a key challenge for sustainable tourism. To explore further the issues of energy use and tourism, the World Bank's LAC region hosted a special session as part of a two day event on sustainable tourism in April 2008. When energy consumption and carbon emissions grow due to the expansion of the tourism industry, so too do the economic benefits in terms of jobs and incomes for the countries of Latin America. To maintain a vibrant and growing tourist industry while reducing the carbon footprint, the session emphasized the need for the region to address two key issues: 'the mitigation of GHG emissions, derived from transport and accommodations activities, and the application of existing and new technologies to improve energy efficiency.' (United Nations World Tourism Organization (UNWTO), 2007) The session therefore highlighted new initiatives in GHG mitigation and innovative uses of renewable energy in LAC's tourism sector. This En Breve describes recent efforts by national governments, the private sector, and international organizations to address the challenges of climate change and carbon emissions in the tourism sector.